Abhängigkeit eines indikationsspezifischen Algorithmus zur Schritterkennung bei Personen mit Multipler Sklerose von Gehgeschwindigkeit und Trageposition - Shammas, Layal; Rashid, Asarnusch; Tallner, Alexander; Hartung, Verena; Streber, René; Wanner, Philipp; Roth, Benjamin; Weiland, A. -C.; Flachenecker, Peter; Mäurer, Mathias; Pfeifer, Klaus (64. Jahrestagung der Deutschen Gesellschaft für Medizinische Informatik, Biometrie und Epidemiologie e.V. (GMDS), 2019)

Akzelerometrie zur Erfassung körperlicher Aktivität. Empfehlungen zur Methodik. - Gabrys, Lars; Thiel, Christian; Tallner, Alexander; Wilms, Britta; Müller, Carsten; Kahlert, Daniela; Darko, Jekauc; Frick, Fabienne; Schulz, Holger; Sprengeler, Ole; Hey, Stefan; Kobel, Susanne; et al. (Sportwissenschaft, 2014)

An Adaptable Inertial Sensor Fusion-Based Approach for Energy Expenditure Estimation. - Schuldhaus, Dominik; Dorn, Sabrina; Leutheuser, Heike; Tallner, Alexander; Klucken, Jochen; Eskofier, Björn (The 15th International Conference on Biomedical Engineering, 2013)

An internet-based at home physical training protocol enhances muscle strength and lung function im multiple sclerosis patients. - Tallner, Alexander; Pfeifer, Klaus; Mäurer, Mathias (Annual Meeting of the American Academy of Neurology, 2011)

An internet-based at home Training Protocol enhances Muscle Strength and lung function in Multiple Sclerosis Patients. - Tallner, Alexander; Mäurer, Mathias; Pfeifer, Klaus (16th annual meeting of the European College of Sport Science, 2011)

A randomized study to evaluate the effect of exercise on fatigue in people with relapsing–remitting multiple sclerosis treated with fingolimod - Maeurer, Mathias; Schuh, Katrin; Seibert, Sabine; Baier, Monika; Hentschke, Christian; Streber, René; Tallner, Alexander; Pfeifer, Klaus (Multiple Sclerosis Journal - Experimental, Translational and Clinical, 2018)
Background Fatigue is a major symptom of multiple sclerosis (MS) in patients, and it has been shown to improve with physical exercise. Although fingolimod might lessen fatigue, it is unclear how patients treated with fingolimod react to physical activity regarding fatigue. Objective This study evaluated the effect of an exercise intervention on fatigue in relapsing–remitting MS patients receiving fingolimod. Methods People with MS (PwMS) were randomized to either a structured internet-based exercise program (e-training) or no e-training intervention. The primary endpoint was the change in the Modified Fatigue Impact Scale (mFIS) after six months. Results The primary analysis showed no statistically significant difference between groups in the mFIS change. Subgroup analyses revealed a beneficial effect of physical exercise for PwMS with low aerobic capacity and with low aerobic capacity plus more severe fatigue. The incidence of adverse events was similar in both groups. No cardiovascular events were reported. The majority of PwMS were relapse free. Conclusion Physical exercise benefits on fatigue may depend on the physical capacity of the patient and requires individualized training. Consistent with previous studies, these results suggest that physical exercise generally does not impose a risk and that this holds true also for patients receiving fingolimod.
Keywords: Multiple sclerosis; fatigue; physical exercise; training; fingolimod; aerobic capacity

Attitudes towards physical activity and digital physical activity promotion in persons with Multiple Sclerosis - Tallner, Alexander; Neumuller, Luise; Pfeifer, Klaus (MULTIPLE SCLEROSIS JOURNAL, 2020)
CRIS-Team WoS Importer:2020-12-18

Behavioral Interventions in MS: a biopsychosocial perspective - Heesen, Christoph; Köpke, Sascha; Kasper, Jürgen; Poettgen, Jana; Tallner, Alexander; Mohr, D C; Gold, Stefan M (Expert review of neurotherapeutics, 2012)

Bewegungsförderung und Sport in der Neurologie – Kompetenzorientierung und Nachhaltigkeit - Pfeifer, Klaus; Sudeck, Gorden; Geidl, Wolfgang; Tallner, Alexander (Neurologie und Rehabilitation, 2013)

Bewegungstherapie bei Multipler Sklerose - Wirkungen von körperlicher Aktivität und Training - Tallner, Alexander; Pfeifer, Klaus (Bewegungstherapie und Gesundheitssport, 2008)
UnivIS-Import:2015-03-09:Pub.2008.phil.dps.iss.psbg.bewegu

Bewegungstherapie in der Neurologie - Tallner, Alexander; Steib, Simon; Pfeifer, Klaus (Physiotherapie, 2013)

Bewegungstherapie in der Neurologie - Tallner, Alexander; Steib, Simon; Pfeifer, Klaus; Schupp, Wilfried (Der Neurologe & Psychiater, 2011)

Bewegungstherapie in der Neurologie - Möglichkeiten und aktuelle Evidenz - Tallner, Alexander (Neurologie und Rehabilitation, 2012)

Bewegungstherapie zur Verbesserung der Mobilität von Patienten mit Multipler Sklerose - Tholen, Reina; Dettmers, Christian; Henze, Thomas; Höthker, Stefan; Flachenecker, Peter; Lamprecht, Sabine; Sailer, Michael; Tallner, Alexander; Vaney, Claude (Neurologie und Rehabilitation, 2019)
Unter der Leitung der Deutschen Gesellschaft für Neurorehabilitation (DGNR) und unter führender Mitarbeit von Reina Tholen vom Physio Deutschland (ehemals ZVK) erfolgte in der Arbeitsgruppe »Leitlinien zur Rehabilitation der MS« der DGNR eine systematische Recherche zu bewegungstherapeutischen Interventionen zur Verbesserung der Mobilität bei Multipler Sklerose (MS

Contributions of physical activity, neurological function and walking speed to cardiovas-cular fitness in ambulatory persons with multiple sclerosis. - Tallner, Alexander; Pfeifer, Klaus; Mäurer, Mathias (17th annual conference of RIMS (Rehabiltation in Multiple Sclerosis), 2012)

COVID-19 outbreak in Germany was associated with a clinically relevant reduction of physical activity levels in persons with multiple sclerosis - Hartung, Verena; Tallner, Alexander; Rashid, Asarnusch; Shammas, Layal; Mäurer, Mathias; Flachenecker, Peter; Pfeifer, Klaus (DGN-Kongress 2020 - Abstracts, 2020)

Ecological validity of the two minute walk test in persons with multiple sclerosis - Weiß, Viktoria; Hartung, Verena; Tallner, Alexander; Streber, René; Wanner, Philipp; Shammas, L.; Rashid, A.; Weiland, A. -C.; Flachenecker, P.; Maeurer, M.; Pfeifer, Klaus (MULTIPLE SCLEROSIS JOURNAL, 2019)
CRIS-Team WoS Importer:2019-10-11

Effects of a behavioural internet-based after-care program on physical activity and self-concordance in persons with Multiple Sclerosis - Streber, René; Gawlik, Angeli; Gusowski, Klaus; Hartung, Verena; Kuld, Sarah; Tallner, Alexander; Wanner, Philipp; Flachenecker, Peter; Pfeifer, Klaus (Multiple Sclerosis Journal, 2018)
Background: Physical activity and exercise (PA) are an important therapeutic component of inpatient rehabilitation for persons with Multiple Sclerosis (pwMS). Internet-based interventions appear promising to enable pwMS to maintain motivation and transfer the acquired knowledge and skills for a physically active lifestyle after inpatient rehabilitation. We evaluated the combined effects of a behavioural internet-based PA promotion program after a multimodal MS-specific rehabilitation on PA levels and exercise-related self-concordance in pwMS. Methods: In this pilot randomized controlled trial, pwMS (age ≥ 18 years, EDSS ≤ 6.0) were randomly assigned after rehabilitation to a three-month intervention (IG), comprising an exercise training module and a blended-learning PA promotion module, or to a control group (CG). The Baecke PA questionnaire and the concordance of sport- and exercise-related goals questionnaire were applied at baseline, at the end of rehabilitation and immediately post-intervention. Within- and between-group changes were analysed with a linear mixed model. Results: 64 pwMS were included in the data analysis (nIG=34, nCG=30). Both the IG (1.00; 95% CI 0.46 to 1.54, p < 0.001) and the CG (0.62; 95% CI 0.06 to 1.19, p < 0.05) significantly increased PA, but no between-group differences in mean change of the sport score (0.37; 95% CI - 0.41 to 1.15, p = 0.35) from baseline to post-intervention were observed. Regarding self-concordance, significant within-group changes were present in the IG (0.97; 95% CI 0.07 to 1.86 p < 0.05) in contrast to the CG (-0.44; 95% CI - 1.39 to 0.51, p = 0.36) and between-group difference were significant (1.41; 95% CI 0.10 to 2.7, p < 0.05) from baseline to post-intervention. Conclusion: This study provides preliminary evidence for the importance of an after-care program to sustain effects on PA but also on self-concordance as an important determinant for long-term PA levels in pwMS. Longer-lasting programs may have more sustained effects
Keywords: physical activity; exercise; rehabilitation; telemedicine; multiple sclerosis; internet

Effects of a behavioural internet-based after-care program on physical activity and self-concordance in persons with Multiple Sclerosis - Streber, René; Gawlik, Angeli; Kuld, Sarah; Gusowski, Klaus; Tallner, Alexander; Hartung, Verena; Wanner, Philipp; Flachenecker, Peter; Pfeifer, Klaus (23rd Annual RIMS Conference MS Rehabilitation across the lifespan, 2018)
Background. Physical activity and exercise (PA) are an important therapeutic component of inpatient rehabilitation for persons with multiple sclerosis (pwMS). Internet-based interventions appear promising to enable pwMS to maintain motivation and transfer the acquired knowledge and skills for a physically active lifestyle into everyday life after inpatient rehabilitation. We evaluated the effects of a behavioural internet-based PA promotion program after a multimodal MS-specific rehabilitation on PA levels and exercise-related self-concordance in pwMS.   Methods. In this pilot randomized controlled trial, pwMS (age ≥ 18 years, EDSS ≤ 6.0) were randomly assigned to a three-month intervention (IG) or to a control group (CG). The Baecke PA questionnaire and the concordance of sport- and exercise-related goals questionnaire were applied at baseline, at the end of rehabilitation and immediately after post-intervention. Effects were analysed with a linear mixed model.   Results. 64 pwMS were included in the data analysis (nIG=34, nCG=30). Both the IG (1.00; 95% CI 0.46 to 1.54, p < 0.001) and the CG (0.62; 95% CI 0.06 to 1.19, p = 0.03) significantly increased PA, but no significant between-group differences in mean change of the sport score (0.37; 95% CI - 0.41 to 1.15, p = 0.35) from baseline to post-intervention were observed. Regarding self-concordance, significant within-group changes were present in the IG (0.97; 95% CI 0.07 to 1.86 p = 0.03) in contrast to the CG (-0.44; 95% CI - 1.39 to 0.51, p = 0.36) and between-group difference in mean change were significant (1.41; 95% CI 0.10 to 2.7, p = 0.03) from baseline to post-intervention.   Discussion. This study provides preliminary evidence for the importance of an after-care program to sustain effects on PA but also on self-concordance as an important determinant for long-term PA levels in pwMS. Longer-lasting programs may have more sustained effects.
Keywords: physical activity; motivation; after-care; rehabilitation; multiple sclerosis; exercise training

Effects of a brief pedometer-based behavioral intervention for individuals with COPD during in-patient pulmonary rehabilitation on 6-weeks and 6-months objectively measured physical activity: study protocol for a randomized controlled trial. - Geidl, Wolfgang; Semrau, Jana; Streber, René; Lehbert, Nicola; Wingart, Silke; Tallner, Alexander; Wittmann, Michael; Wagner, Rupert; Schultz, Konrad; Pfeifer, Klaus (Trials, 2017)
Background Pulmonary rehabilitation programs often fail to substantially enhance long term physical activity in patients with chronic obstructive pulmonary disease (COPD). The reasons for successful physical activity changes in patients with COPD are not well understood. The need to better understand the determinants of physical activity in patients with COPD and effective rehabilitation strategies to improve physical activity is evident. Methods The STAR-study (Stay Active after Rehabilitation) investigates, in a randomized controlled trial, the additional effect of a pedometer-based behavior change intervention during in-patient pulmonary rehabilitation on objectively measured physical activity 6-weeks and 6-months post rehabilitation. The intervention uses the behavior change techniques a) instruction on how, where and when to perform the behavior, b) prompt goal setting for physical activity, c) prompt self-monitoring of behavior and d) feedback on behavior. The primary outcome of physical activity will be measured using a physical activity monitor (Actigraph wGT3X) for a period of seven days, firstly two weeks before rehabilitation begins (t0) as well as 6-weeks and 6-months after rehabilitation (t3, t4). Additionally, to predict physical activity progression after rehabilitation a complex personal diagnostics battery including questionnaires as well as functional assessments is to be carried out at the start and end of rehabilitation (t1, t2). This battery is based on the foundational ideas of the physical activity-related health competence model. 502 patients with COPD aged ≥ 18 and admitted for an approved pulmonary rehabilitation will be enrolled in the STAR-study. Discussion The STAR-study is designed as a randomized controlled trial to gain a better understanding of the personal determinants of physical activity in patients with COPD and to evaluate a pedometer-based physical activity change intervention in the context of in-patient pulmonary rehabilitation. The results enable future identification of patients with COPD who will find it difficult to engage in long term physical activity after rehabilitation. Based on this, intervention strategies to promote physical activity in the content of pulmonary rehabilitation can be optimized.
Keywords: Behavior change intervention; Chronic obstructive pulmonary disease (COPD); Implicit Association Test; Pedometer; Accelerometry; Physical activity-related health competence; Health-Related Quality of Life (HRQoL)

Effects of exercise on fitness and cognition in progressive MS: A randomized, controlled pilot trial. - Briken, Sven; Gold, Stefan M.; Patra, Stefan; Vettorazzi, E; Harbs, D; Tallner, Alexander; Ketels, Gesche; Schulz, Karl-Heinz; Heesen, Christoph (Multiple Sclerosis Journal, 2014)
Background: Exercise may have beneficial effects on both well-being and walking ability in multiple sclerosis (MS). Exercise is shown to be neuroprotective in rodents and may also enhance cognitive function in humans. It may, therefore, be particularly useful for MS patients with pronounced neurodegeneration. Objective: To investigate the potential of standardized exercise as a therapeutic intervention for progressive MS, in a randomized-controlled pilot trial. Methods: Patients with progressive MS and moderate disability (Expanded Disability Status Scale (EDSS) of 4-6) were randomized to one of three exercise interventions (arm ergometry, rowing, bicycle ergometry) for 8-10 weeks or a waitlist control group. We analyzed the drop-out rate as a measure of feasibility. The primary endpoint of the study was aerobic fitness. Secondary endpoints were walking ability, cognitive function as measured by a neuropsychological test battery, depression and fatigue. Results: A total of 42 patients completed the trial (10.6% drop-out rate). Significant improvements were seen in aerobic fitness. In addition, exercise improved walking ability, depressive symptoms, fatigue and several domains of cognitive function. Conclusion: This study indicated that aerobic training is feasible and could be beneficial for patients with progressive MS. Larger exercise studies are needed to confirm the effect on cognition. © 2014 The Author(s).
Keywords: Aerobic exercise; clinical trial; cognition; depression; fatigue; fitness; motor function; multiple sclerosis; progressive multiple sclerosis; rehabilitation; walking ability

Effects of internet-based exercise (e-training) on fatigue and other patient reported behavioural outcomes (PRO) in patients with relapsing-remitting multiple sclerosis (RRMS). - Jäckel, Nathalie; Tallner, Alexander; Virsevci, Ö; Denkinger, N; Sebald, K; Mäurer, Mathias; Lang, Michael; Schreiber, Herbert (31st Congress of the European Committee for Treatment and Research in Multiple Sclerosis (ECTRIMS), 2015)

Effektivität einer App-basierten Reha-Nachsorge mit dem Schwerpunkt Bewegungsförderung bei COPD-Rehabilitand*innen - Limbach, Matthias; Hartung, Verena; Huber, Veronika; Tallner, Alexander; Pfeifer, Klaus; Schultz, Konrad (32. Rehabilitationswissenschaftliches Kolloquium. Deutscher Kongress für Rehabilitationsforschung - Veränderungskultur fördern - Teilhabe stärken - Zukunft gestalten - vom 20. bis 22. Februar 2023 in Hannover, 2023)

Efficacy of an internet-based program (MS Intakt) to promote physical activity after inpatient rehabilitation in persons with multiple sclerosis – a randomized controlled study - Bures, Anna-Karolina; Kuld, Sarah; Weiland, Ann-Christin; Tallner, Alexander; Gusowski, Klaus; Pfeifer, Klaus; Flachenecker, Peter (European Comittee for treatment and research in multiple sclerosis (ECTRIMS), 2017)
Background. Multimodal rehabilitation improves symptoms in persons with multiple sclerosis (PwMS), but these effects diminish with time, despite the well-known positive impact of exercise on fatigue and mobility. We evaluated the efficacy of a 3-month, internet-based e-training program (“MS Intakt”)1 on fatigue, quality of life and mobility in PwMS after inpatient rehabilitation. Methods. Inclusion criteria:  PwMS admitted to inpatient rehabilitation, no relapse / steroid therapy within the last 30 days,  Fatigue (WEIMuS score ≥ 32), age ≥ 18 years, EDSS ≤ 6.0 E-Training group (EG): 3-month home training program,supervised via internet by sport therapists directly after rehabilitation Control group (CG): usual care alone Primary outcome: Fatigue after 3 months (WEIMuS questionnaire2) Secondary outcomes: Quality of life (MSIS-29, EQ-5d), Mobility (2min walking test, 10m WT, Tinetti score), Neuropsychological parameters (alertness) Physical activity (standardized questionnaires), willingness to pay Measurements: T0:within the first week after admission (Baseline), T1: end of rehabilitation (Discharge), T2: follow-up after 3 months (Month 3), T3: follow-up after 6 months (Month 6, via mail) Results: 84 PwMS were included, of whom 64 completed the study At baseline, median WEIMuS scores were higher (indicating a higher degree of fatigue) in EG than in CG, but decreased similarly at discharge in both groups. However, WEIMuS scores increased again in CG at both follow-up measurements, whereas in the etraining group, fatigue further improved at 3 and 6 months. Similarly, MSIS-29 scores were improved in both groups at discharge, but remained stable at month 3 only in the e-training group. The improvements in gait parameters were also more pronounced in EG, particularly for the 2-minute walking test Conclusion: The results of our study demonstrate that the effects of rehabilitation on fatigue, quality of life and mobility can be maintained with an internet-based home training program for up to 3 – 6 months. Further studies are needed to investigate whether longer-lasting programs may have more sustained effects on these disabling symptoms in PwMS.
Keywords: exercise training; multiple sclerosis; inpatient rehabilitation; internet-based

Efficacy of an internet-based program to promote physical activity and exercise after inpatient rehabilitation in persons with multiple sclerosis: A randomized, single-blind, controlled study - Flachenecker, Peter; Bures, Anna Karoline; Gawlik, Angeli; Weiland, Ann Christin; Kuld, Sarah; Gusowski, Klaus; Streber, René; Pfeifer, Klaus; Tallner, Alexander (International Journal of Environmental Research and Public Health, 2020)
Background: Multimodal rehabilitation improves fatigue and mobility in persons with multiple sclerosis (PwMS). Effects are transient and may be conserved by internet-based physical activity promotion programs. Objective: Evaluate the effects of internet-based physical activity and exercise promotion on fatigue, quality of life, and gait in PwMS after inpatient rehabilitation. Methods: PwMS (Expanded Disability Status Scale (EDSS) ≤ 6.0, fatigue: Würzburg Fatigue Inventory for Multiple Sclerosis (WEIMuS) ≥ 32) were randomized into an intervention group (IG) or a control group (CG). After rehabilitation, IG received 3 months of internet-based physical activity promotion, while CG received no intervention. Primary outcome: self-reported fatigue (WEIMuS). Secondary outcomes: quality of life (Multiple Sclerosis Impact Scale 29, MSIS-29), gait (2min/10m walking test, Tinetti score). Measurements: beginning (T0) and end (T1) of inpatient rehabilitation, 3 (T2) and 6 (T3) months afterwards. Results: 64 of 84 PwMS were analyzed (IG: 34, CG: 30). After rehabilitation, fatigue decreased in both groups. At T2 and T3, fatigue increased again in CG but was improved in IG (p < 0.001). MSIS-29 improved in both groups at T1 but remained improved at T2 and T3 only in IG. Gait improvements were more pronounced in IG at T2. Conclusions: The study provides Class II evidence that the effects of rehabilitation on fatigue, quality of life, and gait can be maintained for 3–6 months with an internet-based physical activity and exercise promotion program.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Exercise; Fatigue; Health behavior; Internet-based intervention; Multiple sclerosis; Online systems; Physical activity; Quality of life; Rehabilitation; Walking

Einfluss einer Kühlweste während körperlicher Aktivität auf Körpertemperatur, Leistungsfähigkeit und subjektives Hitzeempfinden bei MS-Patienten - Werner, A; Tallner, Alexander; Pfeifer, Klaus; Mäurer, Mathias (Aktuelle Neurologie, 2009)

Einfluss von körperlicher Aktivität auf die psychische Verfassung von nicht behinderten MS-Patienten - Tallner, Alexander; Mäurer, Mathias Eckhard; Waschbisch, Anne; Hentschke, Christian; Pfeifer, Klaus (Der Nervenarzt, 2009)

Einfluss von körperlicher Aktivität auf Lebensqualität und psychische Gesundheit von Multiple Sklerose Patienten. - Tallner, Alexander; Mäurer, Mathias; Waschbisch, Anne; Hentschke, Christian; Pfeifer, Klaus (Innovation und Rehabilitation - Kommunikation und Vernetzung, 2010)

Exercise-related goals and motives of persons with Multiple Sclerosis in a German Cohort - Streber, René; Geidl, Wolfgang; Tallner, Alexander; Pfeifer, Klaus (Rehabilitation in multiple sclerosis (RIMS), 2015)
Background In contrast to the many positive health effects of physical activity (PA), physical inactivity is common among persons with Multiple Sclerosis (pwMS). Few studies focused on an individual’s motives and goals of exercise participation in that population. Psychometric properties of the german Berner Motiv- und Zielinventar (BMZI) that was primarily designed for adults without chronic diseases as well as motives and goals of sport participation in pwMS were analyzed. Methods Motives and goals were assessed with the BMZI in an online-based survey in Germany (n=1100). It includes 28 items that are rated from 1 - “not at all true for me” to 5 - “very true for me” and covers eight motives. Psychometric properties were analyzed with an exploratory (EFA) and confirmatory factor analysis (CFA). Additionally, the open question for significant other goals and motives that were not covered in the BMZI were analyzed with a qualitative content analysis. Results Health (M=4.0; SD=0.9) and fitness (M=4.1; SD=0.9) are the most significant motives, whereas sociability (MW = 2.2; SD = 1.0) and competition (M = 1.8; SD = 1.0) play a subordinate role. EFA revealed a six-factor structure. CFA provided evidence of an acceptable model fit (e.g. GFI=0.825, RMSEA=0.076). Content analysis revealed several further themes that are more disease-specific. Discussion The BMZI seems to be a reliable and valid instrument to measure multi-dimensional motive profiles in pwMS but potentials for further development for that specific population were identified. Additionally, this work provides the first insight into the exercise-related motives and goals profiles of pwMS in Germany. In combination with other functional and psychological characteristics, the consideration of a person’s exercise-related motives and goals might be helpful designing person-oriented PA promotion strategies.
Keywords: physical activity; exercise; motives; goals; motivation; multiple sclerosis

Fitnesstraining bei Personen mit Multipler Sklerose - Tallner, Alexander; Pfeifer, Klaus (Neurorehabilitation, 2012)

geMeinSam aktiv. Internet-based platform for physical activity promotion in persons with multiple sclerosis. - Streber, René; Tallner, Alexander; Pfeifer, Klaus (SIG Mobility Meeting of Rehabilitation in Multiple Sclerosis, 2014)

Innovative Konzepte: e-Training zur Sicherung der nachhaltigen Bindung an körperliche Aktivität - Peters, Stefan; Tallner, Alexander; Pfeifer, Klaus (Band 101, 2013)

Internet-based exercise and physical activity promotion for persons with multiple sclerosis: a randomized controlled trial - Hartung, Verena; Tallner, Alexander; Flachenecker, Peter; Mäurer, Mathias; Streber, René; Wanner, Philipp; Rashid, Asarnusch; Shammas, Layal; Hois, Gottfried; Dettmers, Christian; Roick, Holger; Stefanou, Alexander; et al. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background: We evaluated the effects of a 12-week internet-based exercise and physical activity promotion program for persons with multiple sclerosis. Methods: We performed a multicenter, randomized, waitlist-controlled study. The intervention group (IG) received the 12-week program, followed by 12 weeks with usual care. The control group (CG) received usual care only. The main components of the 12-week program were: (1) a tailored home-based exercise prescription, (2) e-learning resources, (3) telephone and video meetings with an exercise therapist, (4) the provision of a consumer-based PA monitor. Measurements were taken at baseline, postintervention, and after 24 weeks. The primary outcome was device-measured steps/day. Other outcomes were device-measured moderate-to-vigorous physical activity, subjectively measured leisure-time and transportation physical activity and sport/exercise, physical activity-related health competence, walking ability, quality of life, fatigue, depression, and PA-related self-concordance. We compared changes from baseline to postintervention between groups and analyzed changes in the IG during the follow-up. Results: Analysis of 56 persons with multiple sclerosis (IG: n = 29, CG: n = 27, age: 45.6 ± 10.9) revealed no significant intervention effect on steps/day. However, significant improvements were observed in moderate-to-vigorous physical activity, sport/exercise, control competence, fatigue, and quality of life (physical). During the follow-up, sport/exercise and quality of life decreased significantly. Leisure-time and transportation physical activity increased significantly. Conclusions: Our study provides first evidence that the developed program can increase control competence, aspects of physical activity and health in persons with multiple sclerosis. A trial with a larger sample is recommended to confirm our results and examine intervention mechanisms. Trial registration: Registry: Clinicaltrials.gov; registration number: NCT04367389; date of registration: 2020-04-21 (retrospectively registered).
CRIS-Team Scopus Importer:2025-05-02
Keywords: Behavior change; Exercise; Internet-based intervention; Multiple sclerosis; Physical activity; Physical activity-related health competence

Internetbetreutes körperliches Training verbessert Kraft und Lungenfunktion bei Multiple Sklerose-Patienten - Tallner, Alexander; Mäurer, Mathias; Pfeifer, Klaus (Rehabilitation: Flexible Antworten auf neue Herausforderungen, 2012)
UnivIS-Import:2015-04-16:Pub.2012.phil.dps.iss.psbg.intern

Internetbetreutes Kräftigungs- und Ausdauertraining verbessert Kraft und Lungenfunktion bei Multiple Sklerose- Patienten - Tallner, Alexander; Mäurer, Mathias; Pfeifer, Klaus (Nachhaltigkeit durch Vernetzung, 2011)

Internetgestützte Bewegungsförderung bei Personen mit Multipler Sklerose - Tallner, Alexander; Streber, René; Peters, Stefan; Mäurer, Mathias Eckhard; Pfeifer, Klaus (Neurologie und Rehabilitation, 2013)

Internet-Supported Physical Exercise Training for Persons with Multiple Sclerosis—A Randomised, Controlled Study - Tallner, Alexander; Streber, René; Hentschke, Christian; Morgott, Marc; Geidl, Wolfgang; Mäurer, Mathias; Pfeifer, Klaus (International Journal of Molecular Sciences, 2016)
Physical exercise is effective in improving functional outcomes in persons with multiple sclerosis (pwMS). We evaluated the feasibility and effectiveness of internet-based exercise training (e-training) for pwMS on health-related quality of life (HrQoL). Secondary outcomes were muscle strength, aerobic capacity, lung function, physical activity, and fatigue. This is a randomised, controlled trial with a wait-list control group. Data were collected at baseline, after three and six months, and analysed using a hybrid linear model. One-hundred twenty-six pwMS participated in the home-based aerobic (1×/week) and strength training (2×/week) intervention that was supervised and documented via an internet-platform. The intervention group received e-training for six months, and the control group received e-training after a three months waiting period. Significant differences between the groups were only observed for muscle strength (knee flexion (effect size ES = 0.3, p = 0.003), knee extension (ES = 0.24, p = 0.015)), peak expiratory flow (ES = 0.2, p = 0.039), and sports activity (ES = 0.33, p = 0.001) after three months. E-training had no effect on HrQoL but did on muscle strength, lung function, and physical activity. It is a promising and feasible approach to facilitate large-scale, yet individual, training support.
Keywords: multiple sclerosis; internet; telerehabilitation; resistance training; aerobic training; exercise; physical activity; health-related quality of life; fatigue; lung function

Kann mobile Akzelerometrie die Wirksamkeit von e-Training mit Multiple Sklerose-Patienten belegen? Eine Machbarkeitsstudie. - Schlummer, A; Tallner, Alexander; Daumer, Martin; Pfeifer, Klaus (Annual meeting of the dvs “Sektion Biomechanik, Sportmotorik und Trainingswissen-schaft, 2010)

Konzept eines internetbasierten Programms zur Bewegungsförderung für Personen mit Multipler Sklerose - Gawlik, Angeli; Streber, René; Tallner, Alexander; Gusowski, Klaus; Flachenecker, Peter; Geidl, Wolfgang; Pfeifer, Klaus (Neurologie und Rehabilitation, 2018)
Trotz der vielfältigen positiven Wirkungen körperlicher Aktivität auf die Gesundheit ist ein Großteil von Personen mit Multipler Sklerose (PmMS) überwiegend inaktiv. Insbesondere gelingt es nur wenigen PmMS, im Anschluss an eine stationäre Rehabilitationsmaßnahme die in der Bewegungstherapie erworbenen Kenntnisse und Fertigkeiten für einen eigenverantwortlichen aktiven Lebensstil in den Alltag zu transferieren. Dies ist jedoch eine notwendige Voraussetzung, um langfristig von den positiven Wirkungen der körperlichen Aktivität zu profitieren. Internetbasierte Interventionen können in diesem Zusammenhang geeignet sein, um Bewegung zu fördern und die Nachhaltigkeit der stationären Rehabilitation zu gewährleisten. Derartige Programme existieren bisher jedoch nicht. Dieser Beitrag beschreibt das Konzept einer dreimonatigen internetbasierten Intervention im Anschluss an eine stationäre Rehabilitation zur Förderung der körperlichen Aktivität von PmMS. Aufbauend auf dem Modell der bewegungsbezogenen Gesundheitskompetenz und der Selbstbestimmungstheorie zielt die Intervention auf die Steigerung der motivationalen und volitionalen Voraussetzungen sowie auf die für einen eigenständigen und regelmäßigen aktiven Lebensstil notwendigen Kompetenzen ab. Es beinhaltet mehrere Techniken der Verhaltensänderung und integriert das Konzept der motivierenden Gesprächsführung. Mit dem vorgestellten Programm steht ein internetbasiertes Versorgungsangebot mit professioneller therapeutischer Unterstützung zur Verfügung, welches PmMS beim Aufbau eines körperlich aktiven Lebensstils unterstütze<br
Keywords: motivation; Selbstbestimmungstheorie; Gesundheitskompetenz; motivierende Gesprächsführung

Körperliche Aktivität bei Personen mit Multipler Sklerose in Deutschland - Tallner, Alexander; Mäurer, M; Pfeifer, Klaus (Neurologie und Rehabilitation, 2013)

Körperliche Aktivität und körperliche Funktionsfähigkeit: Erfassung und Wechselwirkungen bei Personen mit Multipler Sklerose. - Tallner, Alexander (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2012)

Körperliche Aktivität und Sport - Tallner, Alexander; Haupts, Michael (Multiple Sklerose : Symptome besser erkennen und behandeln, 2013)

Körperliche Aktivität und Sport von Personen mit Multipler Sklerose – Barrieren und Förderfaktoren - Streber, René; Tallner, Alexander; Pfeifer, Klaus (Neurologie und Rehabilitation, 2013)

Machbarkeit einer 12-wöchigen internetbasierten Reha-Nachsorge für Personen mit COPD mit dem Fokus Bewegungsförderung – ein Studienprotokoll - Hartung, Verena; Limbach, Matthias; Huber, Veronika; Schultz, Konrad; Tallner, Alexander; Pfeifer, Klaus (Abstractband Jahrestagung dvs-Kommission Gesundheit, 2022)

Mental Health in Multiple Sclerosis Patients without Limitation of Physical Function: The Role of Physical Activity. - Tallner, Alexander; Waschbisch, Anne; Hentschke, Christian; Pfeifer, Klaus; Mäurer, Mathias (International Journal of Molecular Sciences, 2015)
Multiple sclerosis (MS) patients, in general, show reduced physical function, physical activity, and quality of life. Positive associations between physical activity and quality of life have been reported. In particular, we were interested in the relation between physical activity and mental health in MS patients without limitation of physical function, since limitations of physical function may influence both physical activity and quality of life. Assessment comprised the Baecke questionnaire on physical activity, the Short Form 36 Health Survey (SF-36), and Beck Depression Inventory (BDI). We ranked our sample according to physical activity into four groups and performed an ANOVA to analyze the relationship between levels of physical activity and health-related quality of life (HRQoL). Then we performed a subgroup analysis and included patients with unlimited walking distance and a score of less than 18 in the BDI. Most active vs. inactive patients were compared for the mental subscales of the SF-36 and depression scores. From 632 patients, 265 met inclusion criteria and hence quartiles were filled with 67 patients each. Active and inactive patients did not differ considerably in physical function. In contrast, mental subscales of the SF-36 were higher in active patients. Remarkable and significant differences were found regarding vitality, general health perception, social functioning and mental health, all in favor of physically active patients. Our study showed that higher physical activity is still associated with higher mental health scores even if limitations of physical function are accounted for. Therefore, we believe that physical activity and exercise have considerable health benefits for MS patients.

Mobile accelerometry as a tool to measure physical activity as outcome parameter for exercise therapy in MS patients: a feasibility study. - Schimpl, M; Schlummer, A; Neuhaus, A; Pfeifer, Klaus; Tallner, Alexander; Morgott, Marc; Daumer, Martin (Annual meeting of the ECTRIMS, 2010)

Mobile accelerometry as a tool to objectively assess fatigue in MS patients. - Schimpl, M; Tallner, Alexander; Neuhaus, A; Daumer, Martin (Annual Meeting of the European Committee for Treatment and Research in Multiple Scle-rosis (ECTRIMS), 2011)

Mobile Akzelerometrie zur Messung körperlicher Aktivität als Outcome bewegungsthe-rapeutischer Studien: eine Machbarkeitsanalyse. - Tallner, Alexander; Daumer, Martin; Schimpl, M; Schlummer, A; Neuhaus, A; Morgott, Marc; Pfeifer, Klaus (Annual Meeting of the dvs “Kommission Gesundheit”, 2010)

MS-int@kt: subgroup analysis of an internet based training on fatigue, quality of life and gait - Bures, Anna-Karolina; Kuld, Sarah; Weiland, Ann-Christin; Tallner, Alexander; Gusowski, Klaus; Pfeifer, Klaus; Flachenecker, Peter (23rd Annual RIMS Conference MS Rehabilitation across the lifespan, 2018)
Background – Persons with Multiple Sclerosis (PwMS) benefit from inpatient multidisciplinary rehabilitation with regard to fatigue and motor performance. To sustain these positive effects an internet based training program was introduced during rehabilitation and performed for 3 months thereafter. Primary endpoint analysis showed that the internet based training could maintain the improvements on fatigue for up to 6 months. Objectives – In order to determine which PwMS revealed the most pronounced response to therapy, we performed a subgroup analysis by stratifying PwMS according to their baseline performance. Methods – 34 PwMS participated in the training group and 30 in the control group. Performance orientated mobility assessment (POMA) for the risk of fall, 10m-walk-test (10mW) and 2 minutes-walk-test (2minW) were measured at the beginning of the inpatient rehabilitation program (T0), at discharge (T1) and 3 month  after the training program (T2). Fatigue (WEIMuS scale) and quality of life (MSIS 29 and EQ-5d visual analog scale) were measured at T0, T1, T2 and 6 months after discharge (T3). With regard to POMA and EQ-5d VAS, PwMS were divided into two groups according to the median value at T0, whereas the dividers for 10mW and 2minW were 7 sec., 14 steps and 168m, respectively. Results – The effects of rehabilitation on fatigue and quality of life were maintained atT2 and T3 in the training group and returned nearly to baseline values in the control group.  The motor performance of the training group also sustained the positive effects of inpatient rehabilitation at T2. Subgroup analysis at T2 according to the baseline performance showed a significant benefit in 10mW seconds and number of steps for PwMS with low performance (p=<0.05). The POMA also revealed a high significant benefit for the PwMS with low performance (p=<0.001) but not in the high performance subgroup. A different result was seen in 2MW where the high performance subgroup maintained high significantly (p=<0.001) in regard to T0. EQ-5d visual analog scale values remained highly significant (p<0.001) at T2 and T3 in the training group but dropped down below baseline in the control group. The subgroup analysis of the training group confirmed these results, being highly significant only for the low performance group. Conclusions – Statistically and clinically meaningful improvement of fatigue, quality of life and motor performance were demonstrated after a 3 month internet based training program (MS int@kt). The most pronounced effects were observed in PwMS with low performance at baseline. The results in the high performance groups may be influenced by ceiling effects. Taken together, an internet based training may be effective for PwMS after rehabilitation to maintain the positive effects of inpatient rehabilitation for at least up to 6 months.
Keywords: physical activity; exercise training; rehabilitation; internet-based; after-care

MS-int@kt: subgroup analysis of an internet-based training on fatigue, quality of life and gait - Gusowski, Klaus; Bures, Anna-Karolina; Kuld, Sarah; Weiland, Ann-Christin; Gawlik, Angeli; Streber, René; Tallner, Alexander; Pfeifer, Klaus; Flachenecker, Peter (Multiple Sclerosis Journal, 2018)
Background: Persons with MS (PwMS) benefit from inpatient multidisciplinary rehabilitatoin with regard to fatigue and motor performance. To sustain the effects, an internet-based training program was introduced during rehabilitation and performed for 3 months thereafter. Primary endpoint analysis showed that the internet-based training could maintain the improvements for up to 6 month. Objectives: In order to determine which PwMS revealed the most pronounced respoonse to therapy, we performed a subgroup analysis by stratifying PwMS according to baseline performance. Methods: 34 PwMS participated in the training group and 30 in control group. Performance oriented mobility assessment (POMA) for the rist of fall, 10m-walk-test (10MWT) and 2-minute-walking test (2MWT) were measured at the beginning of the inpatient rehabiliation program (T0), at discharge (T1) and 3 month after training (T2), Fatigue (WEImuS) and quality of life (MSIS-29 and EQ-5d) were measured at T0, T1, T2 and 6 month after discharge (T3). Siubgroups were divided in low and high performance (POMA and EQ-5d VAS: median value at T0, 10MWT: 7 sec, 14 steps; 2MWT 168m. Results The effects of rehabitation on fatigue and quality of life were maintained at T2 and T3 in the training group. Subgroup analysis of omtor performance at T2 showed a significant benefit in 10MWT and POMA in the low performance group, whereas in 2MWT, the high performance subgroup remained highly significant. The EQ-5d VAS demonstrated highly significant changes in the whole training group as well as in the subgroup with low performance. Discussion: Statistically and clinically meaningful improvements of fatigue, QoL and motor performance were demonstrated after 3 months of internet-based training, with effects being more pronounced in more affected pwMS. An internet-based training program may be effective to maintain the positive effects of inpatient rehabilitation for at least up to 6 months. <
Keywords: physical activity; exercise therapy; rehabilitation; neurology; multiple sclerosis

Multiple Sclerosis relapses are not associated with exercise - Tallner, Alexander; Waschbisch, Anne; Wenny, Ingrid; Schwab, Stefan; Hentschke, Christian; Pfeifer, Klaus; Mäurer, Mathias (Multiple Sclerosis Journal, 2012)

Multiple Sklerose und körperliche Aktivität - Bewegungsmangel verschlechtert den Zustand - Tallner, Alexander; Waschbisch, Anne; Mäurer, Mathias Eckhard; Pfeifer, Klaus (Der Neurologe & Psychiater, 2009)

Multiple Sklerose und körperliche Aktivität - Eine historische Betrachtung - Tallner, Alexander; Mäurer, Mathias; Pfeifer, Klaus (Der Nervenarzt, 2013)
Uncertainties concerning the pathology of multiple sclerosis have in the past led to numerous theories about the cause and therapy of the disease. In the last 40 years technological progress and the use of scientific research methods have contributed to a considerably enlarged body of medical and scientific knowledge, a process that has not yet come to an end. The attitude towards physical activity has also changed tremendously over time. There was a paradigm shift from the fear of triggering and aggravating the disease towards therapeutic benefits of physical activity and exercise. The first evidence for beneficial effects of exercise on symptoms and the course of the disease originated in the 1960s; however, a growing scientific interest in the topic was not recognizable until the 1990s when the number of exercise studies finally started to increase. Nowadays, the positive effects of physical activity and exercise are well established; nevertheless, high-quality research reports are still lacking. As a consequence there are still many unresolved questions concerning specific training effects and recommendations. © Springer-Verlag Berlin Heidelberg 2013.
Keywords: History; Multiple sclerosis; Physical activity; Physical exertion; Therapy

Multiple Sklerose und Sport - Waschbisch, Anne; Tallner, Alexander; Pfeifer, Klaus; Mäurer, Mathias Eckhard (Der Nervenarzt, 2009)

Patientenschulung zu körperlicher Aktivität und Training bei Multipler Sklerose (PakT-MS) - Peters, Stefan; Tallner, Alexander; Pfeifer, Klaus (Bewegungstherapie und Gesundheitssport, 2013)

Periodisiertes Heimtraining: eine neue Strategie, die Adhärenz zu hochintensiver Bewegungstherapie bei Personen mit milder Multipler Sklerose zu verbessern - Tallner, Alexander (Bewegungstherapie und Gesundheitssport, 2019)
CRIS-Team WoS Importer:2020-02-21

Physical Activity in Multiple Sclerosis: A Comparative Study of Vitamin D, BDNF and Regulatory T Cell Populations - Waschbisch, Anne; Wenny, Ingrid; Tallner, Alexander; Schwab, Stefan; Pfeifer, Klaus; Mäurer, Mathias (European neurology, 2012)

Physical activity in persons with multiple sclerosis in Germany - Tallner, Alexander; Mäurer, Mathias; Pfeifer, Klaus (Neurologie und Rehabilitation, 2013)
The positive, health-enhancing effects of physical activity for the general population as well as for persons with chronic diseases are indisputable. In the context of multiple sclerosis, though, potential negative effects of physical exertion have long been in the center of attention. In the meantime, there is an evidence base for benefits of physical activity in multiple sclerosis, but research within Germany is scarce. This is the first study to assess activity behaviour and health-related quality of life in a large sample of persons with MS in Germany. Both constructs were found to be relatively high, with the sample holding an intermediary position between international MS samples and the german healthy population. An explanation for this might be a selection bias that originated from the recruitment strategies that focused outside of clinical settings. Taken the other way round, studies including participants only in clinical settings might suffer from a selection bias as well. © Hippocampus Verlag 2013.
Keywords: Health-related quality of life; Multiple sclerosis; Physical activity

Psychische Verfassung nicht behinderter MS-Patienten - Tallner, Alexander; Waschbisch, Anne; Hentschke, Christian; Pfeifer, Klaus; Mäurer, Mathias (Der Nervenarzt, 2009)

Relation between cognitive function and physical activity in multiple sclerosis patients treated with interferon beta-1b – the CogniPlus study. - Brochet, Bruno; Tallner, Alexander; Penner, Iris-Katharina; Bauer-Steinhusen, Ulrike; Tückmantel, C; Wicklein, E; Langdon, Dawn (31st Congress of the European Committee for Treatment and Research in Multiple Sclero-sis (ECTRIMS), 2015)

Relationship between Physical Activity and Mental Health in Multiple Sclerosis Patients without Limitation of Physical Function: A Cross-Sectional Explorative Study. - Tallner, Alexander; Pfeifer, Klaus; Wenny, Ingrid; Mäurer, Mathias; Waschbisch, Anne (Annual Meeting of the American Academy of Neurology, 2009)

Sensor-based gait analysis using mobile phones is useful for the assessment of fatigue in patients with multiple sclerosis - a proof of concept study - Schoenherr, C.; Strauss, S.; Ziegler, J.; Zentek, T.; Rashid, A.; Tallner, Alexander; Grothe, M. (MULTIPLE SCLEROSIS JOURNAL, 2022)
CRIS-Team WoS Importer:2022-12-09

Sportmotive bei Personen mit Multipler Sklerose - Geidl, Wolfgang; Streber, René; Tallner, Alexander; Pfeifer, Klaus (Band 107, 2015)

Sport und MS. Einfluss von physischer Aktivität auf die Immunregulation. - Waschbisch, Anne; Wenny, Ingrid; Tallner, Alexander; Pfeifer, Klaus; Mäurer, Mathias (Der Nervenarzt, 2010)

The relevance of competences for a healthy, physically active lifestyle in persons with multiple sclerosis (pwMS): A path analytical approach - Carl, Johannes; Hartung, Verena; Tallner, Alexander; Pfeifer, Klaus (Behavioral Medicine, 2021)
To promote health and counteract the decline associated with the disease, persons with multiple sclerosis (pwMS) are advised to lead healthy, physically active lifestyles. The physical activity-related health competence (PAHCO) model posits that individuals must meet three integrated, person-related requirements for the adoption of such a lifestyle: movement competence, control competence, and self-regulation competence. To gain insights into the needs and challenges of pwMS, the goal of the present study was to empirically examine the roles of these competences within this target group. A total of 475 pwMS underwent a multidimensional, online-based assessment of PAHCO. These participants self-reported their amount of physical activity (PA), health status, disease-related, and sociodemographic information. We used a series of path analyses to investigate the relevance of the three competence areas for each individual’s PA level and subjective health. Stepwise multivariate analyses revealed that self-regulation competence was significantly associated with overall PA volume. In contrast, movement competence did not contribute to this prediction. Control competence was also not related to PA level. However, in accordance with the PAHCO model, this factor exerted an independent, qualitative effect on participant health. In summary, self-regulation competence appears to play a crucial role with regard to PA volume. Specifically, control competence appears to be key for the qualitative aspect of PA promotion, characterizing the individual’s application of an appropriate stimulus for the achievement of health. Integrating the promotion of self-regulation and control competences into rehabilitation practices can help to foster healthy, physically active lifestyles in pwMS.<br
Keywords: behavior change; chronic disease; health literacy; physical activity; physical literacy

The two-minute walk test in persons with multiple sclerosis: Correlations of cadence with free-living walking do not support ecological validity - Karle, Viktoria; Hartung, Verena; Ivanovska, Keti; Mäurer, Mathias; Flachenecker, Peter; Pfeifer, Klaus; Tallner, Alexander (International Journal of Environmental Research and Public Health, 2020)
The two-minute walk test (2MWT) is a frequently used walking capacity test in persons with multiple sclerosis (pwMS). However, less is known about its relevance with regards to walking capacity during free-living walking performance. Therefore, the ecological validity of the 2MWT was tested by 1. computing free-living minutes with the same intensity (cadence) as during the 2MWT and 2. investigating the relationship between 2MWT cadence and minutes with the same cadence during free-living walking. 20 pwMS aged 44.2 ± 12.2 (Expanded Disability Status Scale (EDSS) score of 3.1 ± 1.4) performed a 2MWT and wore an accelerometer for seven days. The number of pwMS reaching 100%, 90%, 80% or 70% of 2MWT cadence for at least one minute a day and minutes/day with at least 100%, 90%, 80% and 70% of 2MWT cadence during free-living walking was calculated. Six participants reached 100% of the 2MWT cadence for at least one minute/day during free-living walking. A total of 80% 2MWT cadence was the first intensity category that was reached by all participants during free-living walking. No significant correlation was found between cadence in the 2MWT and minutes in which this cadence was reached during free-living walking. Ecological validity with regard to walking intensity could not be confirmed in our study sample.
CRIS-Team Scopus Importer:2020-12-18
Keywords: Accelerometry; Ecological validity; Free-living walking; Habitual walking; Multiple sclerosis; Two-minute walk test; Walking performance

Using telerehabilitation to support behavior change. - Paul, Lorna; Tallner, Alexander; Kos, Daphne; Renom, Marta (Way Ahead, 2015)

Validierung des Berner Motiv- und Zielinventars im Freizeit- und Gesundheitssport für Personen mit Multipler Sklerose - Streber, René; Geidl, Wolfgang; Tallner, Alexander; Pfeifer, Klaus (Zeitschrift für Sportpsychologie, 2017)
Zusammenfassung. Mit dem Berner Motiv- und Zielinventar (BMZI) liegt ein fragebogenbasiertes, individualdiagnostisches Messinstrument zur Erhebung von zentralen bewegungsrelevanten Motiven von gesunden Erwachsenen im Kontext des Fitness- und Gesundheitssports vor. In der klinischen Population von Personen mit Multipler Sklerose (PmMS) wurden Motive für das Bewegungsverhalten trotz der hohen Bedeutung für das Bewegungsverhalten bisher kaum systematisch untersucht. Gerade in dieser Zielgruppe besteht aber ein Bedarf an wirksamen Interventionen zur Bewegungsförderung. Innerhalb dieser webbasierten Querschnittserhebung mit 1100 Probanden wurde die psychometrische Qualität des BMZI mittels der explorativen wie konfirmatorischen Faktorenanalyse überprüft. Zur Identifikation weiterer Beweggründe wurden zusätzlich Aussagen mittels der qualitativen Inhaltsanalyse ausgewertet. Der globale Modellfit des identifizierten 7-Faktorenmodells ist akzeptabel. Die Faktoren Wettkampf/Leistung, Figur/Aussehen und Kontakt wurden repliziert. Das BMZI ist ein in Teilen reliables und valides Instrument zur Messung der bewegungsbezogenen Motive von PmMS. Die quantitativen wie qualitativen Ergebnisse verdeutlichen einen Adaptionsbedarf des BMZI an die Lebensumstände von PmM
Keywords: Fragebogen; Motivation; körperliche Aktivität; Bewegungsförderung

Validität eines indikationsspezifischen Algorithmus zur Schritterkennung bei Personen mit Multipler Sklerose - Shammas, Layal; Tallner, Alexander; Wanner, Philipp; Streber, René; Hartung, Verena; Weiland, Ann-Christin; Rashid, Asarnusch; Mäurer, Mathias; Pfeifer, Klaus; Flachenecker, Peter (DGN-Kongress 2019 - Abstracts - Stuttgart, 2019)

Validity of consumer activity monitors and an algorithm using smartphone data for measuring steps during different activity types - Hartung, Verena; Sarshar, Mustafa; Karle, Viktoria; Shammas, Layal; Rashid, Asarnusch; Roullier, Paul; Eilers, Caroline; Mäurer, Mathias; Flachenecker, Peter; Pfeifer, Klaus; Tallner, Alexander (International Journal of Environmental Research and Public Health, 2020)
Background: Consumer activity monitors and smartphones have gained relevance for the assessment and promotion of physical activity. The aim of this study was to determine the concurrent validity of various consumer activity monitor models and smartphone models for measuring steps. Methods: Participants completed three activity protocols: (1) overground walking with three different speeds (comfortable, slow, fast), (2) activities of daily living (ADLs) focusing on arm movements, and (3) intermittent walking. Participants wore 11 activity monitors (wrist: 8; hip: 2; ankle: 1) and four smartphones (hip: 3; calf: 1). Observed steps served as the criterion measure. The mean average percentage error (MAPE) was calculated for each device and protocol. Results: Eighteen healthy adults participated in the study (age: 28.8 ± 4.9 years). MAPEs ranged from 0.3–38.2% during overground walking, 48.2–861.2% during ADLs, and 11.2–47.3% during intermittent walking. Wrist-worn activity monitors tended to misclassify arm movements as steps. Smartphone data collected at the hip, analyzed with a separate algorithm, performed either equally or even superiorly to the research-grade ActiGraph. Conclusion: This study highlights the potential of smartphones for physical activity measurement. Measurement inaccuracies during intermittent walking and arm movements should be considered when interpreting study results and choosing activity monitors for evaluation purposes.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Accelerometer; Accuracy; Activities of daily living; Activity trackers; Smartphone; Validation study; Walking

Validity of step detection in persons with MS: evaluation of activity trackers and a disease-specific algorithm using smartphone data - Hartung, Verena; Sarshar, Mustafa; Shammas, Layal; Rashid, Asarnusch; Roullier, Paul; Maeurer, Mathias; Eilers, Caroline; Flachenecker, Peter; Pfeifer, Klaus; Tallner, Alexander (MULTIPLE SCLEROSIS JOURNAL, 2020)
CRIS-Team WoS Importer:2020-12-18

Validity of step detection in persons with MS: evaluation of activity trackers and a disease-specific algorithm using smartphone data - Hartung, Verena; Sarshar, Mustafa; Shammas, Layal; Rashid, Asarnusch; Roullier, Paul; Mäurer, Mathias; Eilers, Caroline; Flachenecker, Peter; Pfeifer, Klaus; Tallner, Alexander (RIMS Digital Conference., 2020)

Web-based interventions in multiple sclerosis: the potential of tele-rehabilitation - Tallner, Alexander; Pfeifer, Klaus; Mäurer, Mathias (Therapeutic Advances in Neurological Disorders, 2016)

www.sport-und-ms.de - Internet-based platform for physical activity promotion in persons with Multiple Sclerosis - Streber, René; Tallner, Alexander; Pfeifer, Klaus (Rehabilitation in multiple sclerosis (RIMS), 2015)
Keywords: multiple sclerosis; physical activity; exercise; social network